2023
DOI: 10.21608/ejhm.2023.285050
|View full text |Cite
|
Sign up to set email alerts
|

Association between COX-2 Gene Polymorphism and Susceptibility to Colon and Rectal Cancer

Abstract: Background: Intestinal cancer the third most prevalent malignancy and leading cause of cancer mortality worldwide, is colorectal cancer (CRC). More than one-third of colorectal cancer cases in Egypt include people under the age of 40 who are found to have the disease at an advanced stage. Due to its function in human tumours, cyclooxygenase (COX), a crucial enzyme in the prostanoid biosynthesis pathway, has drawn a lot of interest. COX-2 regulates cell proliferation, cell transformation, tumour growth, metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
0
1
Order By: Relevance
“…Our study is the first to report the CC-variant frequency in Basrah, which had a low rate among patients with UC (14.1%) and the control group (13.3%). No other Iraqi studies about this SNP were found for comparison, but the results were higher than those reported in Egypt for Arabic patients with colorectal cancer (8%) and a control group (2%) (25). They were also higher than the frequency reported by a study on Jordanian adult patients evaluating aspirin resistance (6.5% in the aspirin responders and 3.3% in the nonresponders) (26).…”
Section: Discussion Discussioncontrasting
confidence: 58%
“…Our study is the first to report the CC-variant frequency in Basrah, which had a low rate among patients with UC (14.1%) and the control group (13.3%). No other Iraqi studies about this SNP were found for comparison, but the results were higher than those reported in Egypt for Arabic patients with colorectal cancer (8%) and a control group (2%) (25). They were also higher than the frequency reported by a study on Jordanian adult patients evaluating aspirin resistance (6.5% in the aspirin responders and 3.3% in the nonresponders) (26).…”
Section: Discussion Discussioncontrasting
confidence: 58%